Women's Careers and Family Formation - Sonia R. Bhalotra; Damian Clarke; Selma Walther (Institute of Labor Economics (IZA), 2022)
This paper discusses research on the relationship between fertility and women's labour force participation. It surveys methods used to obtain causal identification, and provides an overview of the evidence of causal effects in both directions. We highlight a few themes that we regard as important in guiding research and in reading the evidence. These include the importance of distinguishing between extensive and intensive margin changes in both variables; consideration not only of women's participation but also of occupational and sectoral choice and of relative earnings; the relevance of studying dynamic effects and of analysing changes across the lifecycle and across successive cohorts; and of recognizing that women's choices over both fertility and labour force participation are subject to multiple constraints. We observe that, while technological innovations in reproductive health technologies have muted the familycareer tradeoff primarily by allowing women to time their fertility, policy has not achieved as much as it might.
Keywords: J01; J13; O15; 330; fertility; birth spacing; abortion; ART; IVF; contraception; female labour force participation; gender wage gap; job loss; recession